Ethernet networking of data reconstruction and image display for optical tomography system - 277451 Goh, Chiew Loon (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2003